On the commerce of thinking : of books and bookstores - Nancy, Jean-Luc (Book collections on Project MUSE., 2009)
Jean-Luc Nancy's On the Commerce of Thinking concerns the particular communication of thoughts that takes place by means of the business of writing, producing, and selling books. His reflection is born out of his relation to the bookstore, in the first place his neighborhood one, but beyond that any such "perfumery, rotisserie, patisserie," as he calls them, dispensaries "of scents and flavors through which something like a fragrance or bouquet of the book is divined, presumed, sensed." On the Commerce of Thinking is thus not only something of a semiology of the specific cu.